Australian Engineering & ICT Education Support Network. - King, Robin; Koppi, Tony (Office for Learning and Teaching, 2014)
The Australian Engineering & ICT Education Support Network aims to capitalise on the momentum and experience of the Discipline Support Strategy to enlarge and strengthen the academic communities of practice in Engineering and ICT to further embed systematic approaches to quality improvements in learning and teaching.